Hubungan Persepsi Relevansi Materi Ajar Matematika dengan Kecemasan Akademik Siswa SMAN 1 Sentolo - Rafli Ismail Putra, Rafli (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
Academic anxiety in mathematics often hinders student achievement. This study aims to analyze the relationship between students' perception of teaching material relevance and academic anxiety. Using a quantitative correlational design, the study involved 100 students from SMAN 1 Sentolo selected via simple random sampling. Data were collected using the Perception of Relevance Scale and Academic Anxiety Scale. Data analysis used Pearson Product Moment correlation. The results showed that the majority of students had medium perceived relevance (64%) and medium academic anxiety (55%). Hypothesis testing revealed a significant negative relationship between perceived relevance and academic anxiety (r = -0.542; p < 0.05). Perceived relevance contributed 29.3% to the reduction of anxiety. This finding implies that higher perceived relevance of mathematics materials correlates with lower anxiety levels in students. Educators are advised to implement contextual learning emphasizing utility value to help reduce student anxiety